Multiple Fraktur dengan Ruptur Arteri dan Vena Brachialis - Nabila Ulfiani; Mohamad Bayu Sahadewa (CV. Jasa Sukses Abadi, 2021)
Trauma is another word injury that can injure. Trauma is another word injury that can injure. Injury to the bones results in fractures (fractures) and dislocations. Fracture is a condition of bone discontinuity. Fractures are divided according to the contact of the outside world, which includes closed and open fractures. The classic symptoms of fracture are a history of trauma, pain and swelling in the fractured bone, eformity (angulation, rotation, discrepancy), tenderness, crepitus, impaired musculoskeletal function due to pain, broken bone continuity and neurovascular disorders. Fracture is one of the causes of trauma to the blood vessels (vascular). Vascular trauma should be suspected in the case of trauma occurring in areas anatomically traversed by large blood vessels. This case report is a man aged 23 years, having difficulty moving his right and left hands, and right lower leg since ± 12 hours of SMRS. Post traffic accident patients ± 10 hours SMRS. From the examination of the localis status of the right brachii region, it was obtained swelling, hematoma ± 5x4 cm, vulnus laceratum ± 2x0.5 cm; there is tenderness, wick pain and increased pain; Pain-limited ROM. The status of the left brachii localist was obtained by swelling, hematoma in the left brachii region ± 6x3 cm, vulnus laceratum ± 2 cm, pulsation A. Radialis not palpable, cold acral from 1/3 distal to the brachial region to the manus, hypoaesthesias and anesthesia present, limited ROM. Localis status of the femoral region until the right cruris is rotated, vulnus laceratum ± 30 cm, pain-limited ROM. In emergency ward, we treated the patient with oxygen administration through no re-breathing mask with 10 ml of oxygen per-minute, infusion with crystaloid solution, wound irrigation, broad spectrum antibiotic, analgetic and fracture stabilisation with posterior slab. The patient underwent urgent surgery to treat his fracture and neurovascular trauma.